Library Usage Study, the How and What: A Survey of Space Usage at a Mid-Sized Research Library - Nichols, Aaron F.; Philbin, Paul P. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2022)
Objective – The research was conducted to understand better how and what spaces are used in a mid-size academic library. Also, the authors were interested in their users' spatial likes and dislikes and why they gravitated to or avoided specific spaces or floors. The authors also found an opportunity to examine recent renovations that added a connector bridge to a first-year student dorm and the subsequent increase in foot traffic to evaluate its success in meeting users' needs for varied and productive study spaces across the building.Methods – The study used a survey to gauge user satisfaction with the library's space and environment for research, study, and collaborative work. The authors hand-distributed a survey with five multiple-choice and three open-response questions to users over three days (Monday-Wednesday) between 10 am - 4 pm, the busiest days and times in a typical week. The collected surveys were sorted and coded in an Excel spreadsheet and uploaded and analyzed in JMP Pro.Results – The 298 completed responses came from undergraduate students (n=281) who visited the first floor, identified as a collaborative study space (n=144). Respondents showed that they visit the library daily (58%, n=173) and weekly (34%, n=104). Most of the survey participants (98%, n=293) indicated that they pursued academic work in quiet spaces they occupied (75%, n=224). Interestingly enough, the noisiest and quietest floors are the areas most avoided, the first floor-collaborative, noisiest space (54%, n=161) and the third floor-designated as quiet space (18%, n=55). The final survey question invited the respondents to "sound off," with 135 responding; 107 (79%) of them opined on improvements to existing study spaces within the library.Conclusion – This research demonstrated that students value the library as a place to study but are critical of excessive noise and overcrowding in the designated collaborative study areas. Academic libraries should consider balance when designing library study spaces. Librarians and space designers should strive to strike an appropriate balance between seating quality and quantity, acceptable noise levels in designated collaborative and quiet study spaces, and the impacts of environmental factors such as printers, food services, exhibits, art displays, restrooms, and walkways through library study spaces within the library.